May measurement month 2017: Latin America. Issue 6 (June 2020) - Barbosa, Eduardo C.D.; Ramirez, Agustin; Beaney, Thomas; Kobeissi, Elsa; Lopez-Jaramillo, Patricio; Hernánez-Hernández, Rafael; Eibel, Bruna; Lanas, Fernando; Penaherrera, Ernesto; Marin, Marcos; Boggia, José; Ortellado, Jose; et al.
Abstract : Objectives: To raise awareness of blood pressure, measured by number of countries involved, number of people screened, and number of people who have untreated or inadequately treated hypertension. Methods: An opportunistic cross-sectional survey of volunteers aged at least 18 years was carried out in May 2017. Blood pressure measurement, the definition of hypertension and statistical analysis followed the standard May measurement month protocol. Eighteen countries in Latin America and the Caribbean participated in the campaign, providing us with a wide sample for characterization. Results: During May measurement month 2017 in Latin America and the Caribbean, 105 246 individuals were screened. Participants who had cardiovascular disease, 2245 (2.3%) had a prior myocardial infarction, and 1711 (1.6%) a previous stroke, additionally 6760 (6.4%) individuals were diabetic, 7014 (6.7%) current smokers and 9262 (8.8%) reported alcohol intake once or more per week. Mean SBP was 122.7 mmHg and DBP was 75.6 mmHg. After imputation, 42 328 participants (40, 4%) were found to be hypertensive. Conclusion: The high numbers of participants detected with hypertension and the relatively large proportion of participants on antihypertensive treatment but with uncontrolled hypertension reinforces the importance of this annual event in our continent, to raise awareness of the prevention of cardiovascular events.